PENGARUH OPINI AUDIT, SOLVABILITAS, UKURAN KAP DAN LABA/RUGI TERHADAP AUDIT REPORT LAG - Sumartini, Ni Komang Ari; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2014)
Audit report lag is time in finishing job audient until publication date of audit report . This research purposes get proof empirical audit opinion, solvability company, size of public accountant, and profit/loss current year on audit report lag. Research carried on mining company in IDX for period 2009-2012. Sample used were 17 company with 68 financial statement. Samples were taken by purposive sampling. The analysis technique used multiple linear regression. Result shows audit opinion and profit/loss current year have negative effects to audit report lag, meanwhile solvability company and size of public accountant not affect the audit report lag.
Keywords: audit report lag, opinion, solvability